(untitled) (Bangladesh Journal of Medical Education, 2014)
This cross-sectional descriptive study was carried out among the teachers and interns doctors of four medical colleges of Dhaka city in last one year (2010-2011).Data was collected by conveniance sampling. In-depth interview of the teachers were taken to explore their views regarding current situation, what should be, and recommendations for future curriculum about teaching communication skills. Information was collected from interns by semi-structured questionnarie. Alocation of score for response of each item was based on 5 point Likert scale.Total respondents were 249 out of which intern doctors were 218 and 31 were teachers. Teachers were chosen from eight clinical subjects as the conveniance of the researcher. Selected 14 variables of communication skills were used in this study. By reviewing the study it was seen that most of the interns gave opinion that they were not taught communication skills in their cinical classes. It was seen in the study that majority of the teachers confessed that they don’t teach communication skills in stuctured way. All of them agreed that it must be taught in stuctured way and assessed. DOI: http://dx.doi.org/10.3329/bjme.v2i1.18132 Bangladesh Journal of Medical Education Vol.2(1) 2011: 14-17